The Predictive Role of Self-efficacy and Social Support in Nurses'Burnout - SS Vaezfar; MM Azadi; A Akbari Balotanbegan; M Rahimi (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: Burnout as a common phenomenon among nurses is related to a number of factors. The study aimed to determine the role of social support and self-efficacy in the prediction of nurses' burnout.   Material & Methods: It was a descriptive, correlational study. The statistical population consisted of all nurses of Isfahan working in the hospitals of this city in 2011-2012. A total of 165 nurses were recruited by random cluster sampling. Data was collected by Social Support Questionnaire of Samavati & Najarians, General Self-efficacy Questionnaire of Schwarzer & Jerusalem's and Maslash Burnout Inventory (MBI) and analyzed by person correlation & stepwise regression tests using SPSS (v.20).   Results: Social support and self-efficacy were correlated with burnout subscales of personal accomplishment r=0.32 and r=0.47, depersonalization, r=-0.32 and r=-0.23 and emotional exhaustion r=-0.26 and r=-0.27 respectively (P< 0.01). The regression results also showed that self-efficacy and social support predict burnout. Conclusion: The results showed that self-efficacy and social support predict the nurses' burnout. The results would help the hospitals' administrators to reduce the nurses' burnout by awareness of their general self-efficacy and social support.